The Methylation Status and Expression of Epstein-Barr Virus Early Genes BARF1 and BHRF1 in Epstein-Barr Virus-Associated Gastric Carcinomas - Jing Li; Wen Liu; Kui Che; Yan Zhang; Zhenzhen Zhao; Bing Luo (Gastroenterology Research and Practice)
Epstein-Barr virus (EBV) is an important DNA virus which establishes latent infection in human malignancies. Expression of EBV-encoded genes in the associated tumors is strongly modulated by promoter CpG methylation of EBV genome. This study aimed to explore the methylation status of the promoters of EBV BamHI-A rightward frame 1 (BARF1) and BamHI-H rightward open reading frame 1 (BHRF1) and their influence on transcriptional expression, to further understand the roles of BARF1 and BHRF1 in the occurrence of EBV-associated cancer. We evaluated the methylation status of BARF1 and BHRF1 promoters in 43 EBV-associated gastric carcinoma (EBVaGC) tissues and EBV-positive cell lines. Their expressions were evaluated by real-time quantitative PCR. We found that the promoters of BARF1 and BHRF1 were methylated by varying degrees in different EBV-positive cell lines and were almost hypermethylated in all EBVaGC tissues. The methylation status of BARF1 and BHRF1 promoters were significantly reduced by 5-Aza-CdR along with the increasing gene expressions. Hypermethylation of Ap and Hp mediates the frequent silencing of BARF1 and BHRF1 in EBV-associated tumors, which could be reactivated by a demethylation agent, suggesting that promoter demethylation and activation is important for BARF1 and BHRF1 transcription and their further action.